Silica‐Based Nanoparticles as Drug Delivery Vehicles for Prostate Cancer Treatment. Issue 6 (15th December 2020) - Tiburcius, Steffi; Krishnan, Kannan; Yang, Jae‐Hun; Hashemi, Fatemeh; Singh, Gurwinder; Radhakrishnan, Deepika; Trinh, Hoang Trung; Verrills, Nicole M.; Karakoti, Ajay; Vinu, Ajayan
Abstract: Prostate cancer (PCa) is one of the most commonly diagnosed cancers and is the fifth common cause of cancer‐related mortality in men. Current methods for PCa treatment are insufficient owing to the challenges related to the non‐specificity, instability and side effects caused by the drugs and therapy agents. These drawbacks can be mitigated by the design of a suitable drug delivery system that can ensure targeted delivery and minimise side effects. Silica based nanoparticles (SBNPs) have emerged as one of the most versatile materials for drug delivery due to their tunable porosities, high surface area and tremendous capacity to load various sizes and chemistry of drugs. This review gives a brief overview of the diagnosis and current treatment strategies for PCa outlining their existing challenges. It critically analyzes the design, development and application of pure, modified and hybrid SBNPs based drug delivery systems in the treatment of PCa, their advantages and limitations. Abstract : Silica based nanoparticles (SBNPs) have emerged as a multipurpose platform for drug delivery applications. Specific characteristics of SBNPs such as tunable porosity, high specific surface area, ease of grafting imaging and targeting moieties and their biocompatibility make them an ideal material for drug delivery applications. This review analzses the recent progress in the use of SBNPs as drug delivery agents for the treatment of prostate cancer including stimuli responsive and targeting strategies of drug delivery.